New Cholesteryl Ester Transfer Protein from Indonesian Herbal Plants as Candidate Treatment of Cardiovascular Disease - Yudhani, Ratih Dewi; Fahrurrozi, Khariz; Indarto, Dono (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: There is a strong negative relationship between high-density lipoprotein cholesterol (HDL-C) and the risk of cardiovascular disease (CVD). Cholesterol ester transfer protein (CETP) is a glycoprotein transporter that transfers cholesterol esters to very low-density lipoprotein and low-density lipoprotein cholesterol (LDL-C). The CETP inhibitor is a new strategy against CVD because of its ability to increase HDL-C. Various Indonesian plants have not been optimally used, and in silico phytochemical screening of these plants showing potential as CETP inhibitors is still limited. AIM: This study for exploring Indonesian phytochemicals as CETP inhibitors for new CVD treatments. METHODS: We screened 457 phytochemicals registered in the herbal database and met Lipinski’s rule of five. Their molecular structures were downloaded from the PubChem database. The three-dimensional structures of CETP and dalcetrapib (the CETP inhibitor standard) were obtained from a protein data bank (http://www.rcsb.org/pdb/) with the 4EWS code and ZINC database with the ZINC03976476 code, respectively. CETP–dalcetrapib binding complexes were validated 5 times using AutoDock Vina 1.1.2 software. Interactions between CETP and phytochemicals were molecularly docked with the same software and visualized using Pymol 1.8× software. RESULTS: Dalcetrapib had a docking score of −9.22 kcal/mol and bound to CETP at Ser230 and His232 residues. The 11 phytochemicals had lower binding scores than dalcetrapib, but only L-(+)-tartaric acid, chitranone, and oxoxylopine could interact with CETP at the Ser230 residue. These are commonly found in Tamarindus indica, Plumbago zeylanica, and Annona reticulata, respectively. CONCLUSION: L-(+)-Tartaric acid, chitranone, and oxoxylopine show potential as CETP inhibitors in silico.